Improving the efficiency of blasting operations in mines with the help of emulsion explosives - Lyashenko, V; Vorob’ev, A; Nebohin, V; Vorob’ev, K (National Mining University, 2018)
Purpose. To improve the efficiency of blasting operations in mines taking into consideration the upgrading of equipment used to charge blastholes as well as application of high-productive mining equipment of new generation. Methods. The activities used mine experimental pressure-charged blasts to break oversize material as well as mine experimental analysis of blasthole charging to estimate the improvement of efficiency of the emulsion explosives (EEs). Findings. It has сbeen determined that both sticked and bulk emulsion explosives of Ukrainit-PP-2 type as well as new options of charging facilities have following technological characteristics: availability of unique space-saving designs of two-component piston dosing pumps of double-action EE components; sufficiently high efficiency of blasthole charging being up to 60 kg of EE/min; ease of service and maintenance; rather long overhaul period of EE components as for the dosing pump as well as cheapness of attachable equipment; availability of both electronic and visual means to control EE preparation and charging. Originality. It has been proved that the improvement of blasting operations in mines results from the intensified technological processes of blasthole charging characterized by the use of such high-productive self-propelled and space-saving facilities of new generation as machines of ZEVS-1 model and portable charges of ZEP-15 type as well as the use of such environmentally friendly bulk trinitrotoluene-free emulsion explosives as Ukrainit-PP-2. Practical implications. Use of EEs in the process of mine blasting operations provides safety, high-quality rock breakage and fragmentation in the context of minimum toxicity of rock, breakage of rocks having any hardness and water content. Moreover, their use is economically efficient.

Мета. Підвищення ефективності виконання вибухових робіт за допомогою емульсійних вибухових речовин на шахтах з урахуванням вдосконалення обладнання для заряджання вибухових свердловин, а також застосування високопродуктивної гірничої техніки нового покоління. Методика. В роботі для оцінки підвищення ефективності виробництва вибухових робіт за допомогою емульсійних вибухових речовин на шахтах використані шахтні експериментальні вибухи накладного заряду при руйнуванні негабариту й шахтні експериментальні дослідження процесу заряджання шпурів. Результати. Встановлено, що патроновані та наливні емульсійні вибухові речовини (ЕВР) типу Україніт-ПП-2 і нові варіанти зарядних машин мають наступні технологічні особливості: наявність у своєму складі оригінальних малогабаритних конструкцій двокомпонентних поршневих насосів-дозаторів компонентів ЕВР подвійної дії; досить високу продуктивність заряджання свердловин – до 60 кг ЕВР/хв; простоту в обслуговуванні та ремонтах; досить високе напрацювання до капремонту насосу-дозатора компонентів ЕВР, а також значно меншу вартість навісного обладнання; наявність як електронних, так і візуальних засобів контролю за приготуванням і заряджанням ЕВР. Наукова новизна. Доведено, що підвищення ефективності виробництва вибухових робіт на шахтах досягається інтенсифікацією технологічних процесів заряджання вибухових свердловин, що відрізняються застосуванням високопродуктивної самохідної та малогабаритної техніки нового покоління, таких як машини моделі ЗЕВС-1 і переносні зарядники моделі ЗЕП-15 та використанням наливних, екологічно чистих, безтротилових ЕВР Україніт-ПП-2. Практична значимість. Застосування ЕВР на шахтах при веденні вибухових робіт забезпечує без-небезпечне ведення робіт, високу якість відбійки і дроблення гірських порід при мінімальній токсичності, руйнування гірської породи будь-якої міцності й обводненості та економічну ефективність.

Цель. Повышение эффективности производства взрывных работ с помощью эмульсионных взрывчатых веществ на шахтах с учетом совершенствования оборудования для заряжания взрывных скважин, а также применения высокопроизводительной горной техники нового поколения. Методика. В работе для оценки повышения эффективности производства взрывных работ с помощью эмульсионных взрывчатых веществ на шахтах использовались шахтные экспериментальные взрывы накладного заряда при разрушении негабарита и шахтные экспериментальные исследования процесса заряжания шпуров. Результаты. Установлено, что патронированные и наливные эмульсионных взрывчатых веществ (ЭВВ) типа Украинит-ПП-2 и новые варианты зарядных машин имеют следующие технологические особенности: наличие в своем составе оригинальных малогабаритных конструкций двухкомпонентных поршневых насосов-дозаторов компонентов ЭВВ двойного действия; достаточно высокую производительность заряжания скважин – до 60 кг ЭВВ/мин; простоту в обслуживании и ремонтах, достаточно высокую наработку до капремонта по насосу-дозатору компонентов ЭВВ, а также значительно меньшую стоимость навесного оборудования; наличие как электронных, так и визуальных средств контроля за приготовлением и заряжанием ЭВВ. Научная новизна. Доказано, что повышение эффективности производства взрывных работ на шахтах достигается интенсификацией технологических процессов заряжания взрывных скважин, отличающихся применением высокопроизводительной самоходной и малогабаритной техники нового поколения, таких как машины модели ЗЭВС-1 и переносные зарядчики модели ЗЭП-15 и использованием наливных, экологически чистых, бестротиловых ЭВВ Украинит-ПП-2. Практическая значимость. Применение ЭВВ на шахтах при ведении взрывных работ обеспечивает безопасное ведение работ, высокое качество отбойки и дробления горных пород при минимальной токсичности, разрушение горной породы любой степени крепости и обводненности и экономическую эффективность.
Keywords: blasting operations; emulsion explosives; equipment; portable charger; charging machines; safety